MAYBE Initial complexity problem: 1: T: (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ 29 >= a ] (?, 1) f2(a, b, c) -> f300(a, b - 1, c) [ a >= 30 ] (?, 1) f300(a, b, c) -> f2(a, b, c) [ 19 >= b ] (?, 1) f300(a, b, c) -> f1(a, b, d) [ b >= 20 ] (1, 1) f3(a, b, c) -> f300(a, b, c) start location: f3 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ 29 >= a ] (?, 1) f2(a, b, c) -> f300(a, b - 1, c) [ a >= 30 ] (?, 1) f300(a, b, c) -> f2(a, b, c) [ 19 >= b ] (1, 1) f3(a, b, c) -> f300(a, b, c) start location: f3 leaf cost: 1 Applied AI with 'oct' on problem 2 to obtain the following invariants: For symbol f2: -X_2 + 19 >= 0 This yielded the following problem: 3: T: (1, 1) f3(a, b, c) -> f300(a, b, c) (?, 1) f300(a, b, c) -> f2(a, b, c) [ 19 >= b ] (?, 1) f2(a, b, c) -> f300(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f300(a, b, c) with all transitions in problem 3, the following new transition is obtained: f3(a, b, c) -> f2(a, b, c) [ 19 >= b ] We thus obtain the following problem: 4: T: (1, 2) f3(a, b, c) -> f2(a, b, c) [ 19 >= b ] (?, 1) f300(a, b, c) -> f2(a, b, c) [ 19 >= b ] (?, 1) f2(a, b, c) -> f300(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f2(a, b, c) -> f300(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 ] with all transitions in problem 4, the following new transition is obtained: f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] We thus obtain the following problem: 5: T: (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (1, 2) f3(a, b, c) -> f2(a, b, c) [ 19 >= b ] (?, 1) f300(a, b, c) -> f2(a, b, c) [ 19 >= b ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 Testing for reachability in the complexity graph removes the following transition from problem 5: f300(a, b, c) -> f2(a, b, c) [ 19 >= b ] We thus obtain the following problem: 6: T: (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] (1, 2) f3(a, b, c) -> f2(a, b, c) [ 19 >= b ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b, c) [ 19 >= b ] with all transitions in problem 6, the following new transitions are obtained: f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] We thus obtain the following problem: 7: T: (1, 4) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] with all transitions in problem 7, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 2, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 ] We thus obtain the following problem: 8: T: (1, 6) f3(a, b, c) -> f2(a, b - 2, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 2, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 ] with all transitions in problem 8, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 3, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 ] We thus obtain the following problem: 9: T: (1, 8) f3(a, b, c) -> f2(a, b - 3, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 3, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 ] with all transitions in problem 9, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 4, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 ] We thus obtain the following problem: 10: T: (1, 10) f3(a, b, c) -> f2(a, b - 4, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 4, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 ] with all transitions in problem 10, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 5, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 ] We thus obtain the following problem: 11: T: (1, 12) f3(a, b, c) -> f2(a, b - 5, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 5, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 ] with all transitions in problem 11, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 6, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 ] We thus obtain the following problem: 12: T: (1, 14) f3(a, b, c) -> f2(a, b - 6, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 6, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 ] with all transitions in problem 12, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 7, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 ] We thus obtain the following problem: 13: T: (1, 16) f3(a, b, c) -> f2(a, b - 7, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 7, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 ] with all transitions in problem 13, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 8, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 ] We thus obtain the following problem: 14: T: (1, 18) f3(a, b, c) -> f2(a, b - 8, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 8, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 ] with all transitions in problem 14, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 9, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 ] We thus obtain the following problem: 15: T: (1, 20) f3(a, b, c) -> f2(a, b - 9, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 9, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 ] with all transitions in problem 15, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 10, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 ] We thus obtain the following problem: 16: T: (1, 22) f3(a, b, c) -> f2(a, b - 10, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 10, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 ] with all transitions in problem 16, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 11, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 /\ -b + 29 >= 0 /\ 19 >= b - 11 ] We thus obtain the following problem: 17: T: (1, 24) f3(a, b, c) -> f2(a, b - 11, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 /\ -b + 29 >= 0 /\ 19 >= b - 11 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 11, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 /\ -b + 29 >= 0 /\ 19 >= b - 11 ] with all transitions in problem 17, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 12, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 /\ -b + 29 >= 0 /\ 19 >= b - 11 /\ -b + 30 >= 0 /\ 19 >= b - 12 ] We thus obtain the following problem: 18: T: (1, 26) f3(a, b, c) -> f2(a, b - 12, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 /\ -b + 29 >= 0 /\ 19 >= b - 11 /\ -b + 30 >= 0 /\ 19 >= b - 12 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b, c) -> f2(a, b - 12, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 /\ -b + 29 >= 0 /\ 19 >= b - 11 /\ -b + 30 >= 0 /\ 19 >= b - 12 ] with all transitions in problem 18, the following new transition is obtained: f3(a, b, c) -> f2(a, b - 13, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 /\ -b + 29 >= 0 /\ 19 >= b - 11 /\ -b + 30 >= 0 /\ 19 >= b - 12 /\ -b + 31 >= 0 /\ 19 >= b - 13 ] We thus obtain the following problem: 19: T: (1, 28) f3(a, b, c) -> f2(a, b - 13, c) [ 19 >= b /\ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 /\ -b + 20 >= 0 /\ 19 >= b - 2 /\ -b + 21 >= 0 /\ 19 >= b - 3 /\ -b + 22 >= 0 /\ 19 >= b - 4 /\ -b + 23 >= 0 /\ 19 >= b - 5 /\ -b + 24 >= 0 /\ 19 >= b - 6 /\ -b + 25 >= 0 /\ 19 >= b - 7 /\ -b + 26 >= 0 /\ 19 >= b - 8 /\ -b + 27 >= 0 /\ 19 >= b - 9 /\ -b + 28 >= 0 /\ 19 >= b - 10 /\ -b + 29 >= 0 /\ 19 >= b - 11 /\ -b + 30 >= 0 /\ 19 >= b - 12 /\ -b + 31 >= 0 /\ 19 >= b - 13 ] (1, 3) f3(a, b, c) -> f2(a, b - 1, c) [ 19 >= b /\ -b + 19 >= 0 /\ 29 >= a ] (?, 2) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ a >= 30 /\ 19 >= b - 1 ] (?, 1) f2(a, b, c) -> f2(a, b - 1, c) [ -b + 19 >= 0 /\ 29 >= a ] start location: f3 leaf cost: 1 Complexity upper bound ? Time: 1.426 sec (SMT: 1.323 sec)